A Survey of Assets Growth Models in Prediction of the Rank of Liquidity - Delkhosh, Mohammad; Abdollah, Esmat Zade (International Journal of Economics and Financial Issues, 2017)
The present study aims to evaluate the relationship between asset growth in prediction of the rank of liquidity of the stock of companies listed on Tehran Stock Exchange (TSE). Due to various criteria of assets growth, in this study, Cooper et al. (2008), Lyandres et al. (2008) and Zhang et al. (2008) models are used. To do this, four hypotheses are formulated for this issue and the data of 122 TSE companies during 2009-2014 are analyzed. The statistical methodology is correlation and for data analysis, regression is applied. The results of study show that the one-year asset growth criteria of Cooper et al. (2008) two-year growth variable of Cooper et al.(2008) and investment growth variable of Lyandres cannot be good predictors for stock liquidity rank. The variable of Zhang et al. (2008) cannot be a good predictor for stock liquidity rank. Zhang growth variable is a good predictor for the rank of liquidity and it is based on capital expenses in Iranian companies. Keywords: Asset growth, Capital expenses, Rank of liquidity JEL Classifications: G1, G3